PKM Pengembangan Desa Wisata Berbasis Pemberdayaan Masyarakat Menuju Kemandirian Ekonomi Desa di Kabupaten Gresik - Moh. Khoirul Fatih; Nur Hakim (GUYUB: Journal of Community Engagement, 2023)
The development of the country through tourism development is currently a priority program for the central and regional governments. This is not unusual considering the country's economic condition which has experienced a decline after the Covid pandemic over the last two years. The development of tourism villages carried out by the government of Sekapuk Village, Ujungpangkah District, Gresik Regency is one part of the village government's plan to improve the community's economy. The main problem currently being faced is the lack of skills and productivity of community micro, small and medium enterprises as well as the management of PIRT and the legality of MSME products. that has been produced. Empowerment with the title development of tourism villages based on community empowerment towards economic independence aims to 1) alleviate community poverty through sustainable development of community micro, small and medium enterprises, 2) assist in analyzing the potential and realization of micro, small and medium enterprises oriented towards community empowerment towards economic independence. The approach used in this empowerment is a collaborative PAR (Participatory Action Research) approach between researchers and the community to formulate joint problems, plan and carry out joint actions to solve existing problems in a sustainable manner.